Effect Effect Effect Effect Effect Effect Effect of Thickness on Some Physical PropertiesThickness on Some Physical PropertiesThickness on Some Physical PropertiesThickness on Some Physical PropertiesThickness on Some Physical Properties Thickness on Some - Abdul-Ameer Al-Rehamey, Haidar Jwad; F. Al-Hilli, Muthafar; Kh.Rasheed, Hussein (Iraqi Journal of Science, 2023)
The effect of thickness variation on some physical properties of hematite α-Fe2O3 thin films was investigated. An Fe2O3 bulk in the form of pellet was prepared by cold pressing of Fe2O3 powder with subsequent sintering at 800 . Thin films with various thicknesses were obtained on glass substrates by pulsed laser deposition technique. The films properties were characterized by XRD, and FT-IR. The deposited iron oxide thin films showed a single hematite phase with polycrystalline rhombohedral crystal structure .The thickness of films were estimated by using spectrometer to be (185-232) nm. Using Debye Scherrerś formula, the average grain size for the samples was found to be (18-32) nm. Atomic force microscopy indicated that the films had smooth surfaces, with a lateral grain shape. The optical absorption of the films was determined from spectrophotometric measurements.